Enhanced Efficiency Urea Sources and Placement Effects on Nitrous Oxide Emissions. (1st January 2015) - Gao, Xiaopeng; Asgedom, Haben; Tenuta, Mario; Flaten, Donald N.
Abstract : The effects of band placement of enhanced efficiency fertilizers (EEF) on nitrous oxide (N2 O) emissions are uncertain. Placement and EEF on N2 O emissions from spring wheat ( Triticum aestivum L.) at two locations in Manitoba, in 2011 and 2012 were examined. Treatments were a no N control and 80 kg N ha −1 at planting of five combinations of placement and granular N source: broadcast‐incorporated urea (UreaI ) and, subsurface side‐banded urea (UreaS ; each row side‐banded), midrow‐banded urea (UreaM ; placement between every other set of rows), midrow‐banded environmentally smart nitrogen (ESN, Agrium, Inc.) (ESNM ), and midrow‐banded SuperU (Koch Industries Inc.) (SuperUM ). Planting in 2011 was delayed 40 d compared to 2012. Planting coincided with higher soil temperature and moisture resulting in three‐ to sevenfold more growing season N2 O emissions (∑N2 O) in 2011 than 2012. In 2011, SuperUM and ESNM reduced ∑N2 O, emission factor (EF) scaled by N‐applied EF, and yield‐scaled N2 O emission intensity (EI) by 47, 67, and 55%, respectively, compared with UreaI . In 2011, increasing placement concentration of N in order broadcast‐incorporation, side‐banding, and midrow‐banding tended to decrease ∑N2 O, EF, and EI of granular urea, but not statistically significant. The ∑N2 O and nitrate exposure (NE), were significantly correlated over the site‐years, indicating N availability from treatments in part determined emissions. Grain yield and crop N uptake were unaffected by sources and placement. These results suggest for early season wet and warm conditions, EEF N sources can reduce emissions compared with granular urea. Further studies are required to clarify placement effects on N2 O emissions.